2006
DOI: 10.1291/hypres.29.897
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Diastolic Dysfunction as Assessed by Echocardiography in Metabolic Syndrome

Abstract: The purpose of the present study was to elucidate the cardiac structure and function in patients who have metabolic syndrome but no history of cardiovascular disease by analyzing echocardiographic findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
48
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 27 publications
12
48
0
1
Order By: Relevance
“…All these changes result in the onset of LV There is a dilemma as to whether the levels of glucose and glycated hemoglobin affect the global LV function. Studies have confirmed that this correlation exists 3,5,19 , which was also the result of our study. The separate analysis of the influence MS components in our study also showed that fasting glucose levels, in addition to systolic blood pressure and triglycerides levels, were independently associated with the Tei index.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…All these changes result in the onset of LV There is a dilemma as to whether the levels of glucose and glycated hemoglobin affect the global LV function. Studies have confirmed that this correlation exists 3,5,19 , which was also the result of our study. The separate analysis of the influence MS components in our study also showed that fasting glucose levels, in addition to systolic blood pressure and triglycerides levels, were independently associated with the Tei index.…”
Section: Discussionsupporting
confidence: 92%
“…Triglycerides levels were not independently associated with the Tei index when all clinical and echocardiographic parameters were considered. However, when only MS criteria were considered, triglycerides were independently associated with this index, which is consistent with the findings of other authors 5,19 . Fuentes et al 24 were the first to show that subjects with increased levels of triglycerides had significantly impaired LV diastolic function and increased LV mass, when compared to the control group.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations